Celastrol Suppresses Glioma Vasculogenic Mimicry Formation and Angiogenesis by Blocking the PI3K/Akt/mTOR Signaling Pathway - Zhu, Yingjun; Liu, Xihong; Zhao, Peiyuan; Zhao, Hui; Gao, Wei; Wang, Lei (Frontiers in Pharmacology, 2020)
Angiogenesis and vasculogenic mimicry (VM) are thought to be the predominant process for tumor blood supply in the growth and metastasis of glioblastoma (GBM). Celastrol has potential anti-glioma effects, however the mechanism underlying its action remains unclarified. Recent studies showed that the signalling pathway of PI3K/Akt/ mTOR is closely related to angiogenesis and VM formation. In the present study, by the treatment of celastrol, tumor growth was suppressed, tight junction and basal lamina structures in tumor microvasculature was disarranged in U87 glioma orthotopic xenografts in nude mice. Periodic Acid Staining (PAS)- platelet EC adhesion molecule-31 (PECAM-1/CD31) staining revealed celastrol inhibited both VM and angiogenesis in tumor tissues. Additional, celastrol reduced angiogenesis-related proteins, CD31, vascular endothelial growth factor receptor (VEGFR) 2, angiopoietin (Ang) 2 and VEGFA, VM-related proteins, ephrin type-A receptor (EphA) 2 and vascular endothelial (VE)-cadherin expression level. Hypoxia inducible factor (HIF)-1α, phosphorylation of PI3K, Akt and mTOR were also downregulated by the treatment with celastrol. In vitro, we further demonstrated that celastrol inhibited cell growth, migration, invasion in U87 and U251 cells, disrupted VM formation and blocked the activity of PI3K, Akt and mTOR. Collectively, our data suggested that celastrol inhibited VM formation and angiogenesis likely via regulating PI3K/Akt/mTOR signalling pathway.